Exploration of Leisure Constraints Perception in the Context of a Pandemic: An Empirical Study of the Macau Light Festival - Li, Xi; Liu, Jiamin; Su, Xinwei; Xiao, Yinan; Xu, Changbin (Frontiers in Psychology, 2022)
Individuals' capacity to participate in leisure activities is contingent upon their ability to overcome obstacles. It is worthwhile to investigate how individuals perceive constraints on their leisure activities participation during the COVID-19 pandemic. This study demonstrates that the connotation of leisure constraints during pandemic includes personal health concerns, shock on economic revenue, reduced freedom of travel, and inconvenience associated with epidemic prevention. Reduced travel freedom is the most influential factor on participation intentions, followed by personal health concerns. Significant differences in perceptions of constraints are observed between groups with different characteristics.